POTENSI TUMBUHAN BABOTEK (Cardiospernum halicacabum L.) SEBAGAI ANTIBAKTERI - Yasinta Moi, Maria; Dorteia Da Cruz, Ijilda (Jurnal Biogenerasi, 2025)
Babotek plant (Cardiospernum halicacabum L.) is one of the plants utilized by the ethnic community of Dualaus Village, Belu Regency, East Nusa Tenggara, as a traditional medicinal plant to treat diarrhea, flu, fever, and rheumatism. This research aims to test whether the Babotek plant has the ability to act as an antibacterial agent in inhibiting the growth of pathogenic bacteria. The antibacterial activity test method employed the disk diffusion method with plant extract concentrations of 10 ppm, 30 ppm, and 60 ppm, chloramphenicol antibiotic as a positive control, and Aquadest as a negative control. The extraction method used was a stepwise maceration method with ethyl acetate as the solvent. The research results obtained show that the ethyl acetate extract of the Babotek plant is capable of inhibiting the growth of the pathogenic bacteria Staphylococcus epidermidis, with an inhibition zone diameter of 8.2 mm at a concentration of 60 ppm; 7.8 mm at a concentration of 30 ppm; while no inhibition zone was formed at a concentration of 10 ppm. Antibacterial compounds produced by the Babotek plant in inhibiting the growth of test bacteria fall into the moderate category. This research is expected to contribute to efforts to improve public health quality and develop local community wisdom scientifically, as well as the sustainable use of plants.